2006
DOI: 10.1175/jtech1957.1
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Profiling Using Atmospheric Radiation Measurement Program Vertically Pointing 8-mm Wavelength Radars

Abstract: An attenuation-based method to retrieve vertical profiles of rainfall rate from vertically pointing K a -band radar measurements has been refined and adjusted for use with the U.S. Department of Energy's cloud radars deployed at multiple Atmospheric Radiation Program (ARM) test bed sites. This method takes advantage of the linear relationship between the rainfall rate and the attenuation coefficient, and can account for a priori information about the vertical profile of nonattenuated reflectivity. The retrieva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 22 publications
0
18
1
Order By: Relevance
“…Matrosov (2005) demonstrated that at 35 GHz there is a nearly linear relation between specific attenuation (A) and R. The linearity of this relation and its low sensitivity to the DSD details is explained by the fact that at Ka band both A and R are approximately proportional to the 3.65th DSD moment (Matrosov et al, 2006). These authors used this relation to retrieve layer-average rain rates from a vertically pointing Ka-band radar and showed that relative retrieval errors generally increase for lighter rainfall when reflectivity changes due to attenuation become smaller compared to vertical changes of non-attenuated reflectivity.…”
Section: A-r Based Rain Rate Estimationmentioning
confidence: 99%
“…Matrosov (2005) demonstrated that at 35 GHz there is a nearly linear relation between specific attenuation (A) and R. The linearity of this relation and its low sensitivity to the DSD details is explained by the fact that at Ka band both A and R are approximately proportional to the 3.65th DSD moment (Matrosov et al, 2006). These authors used this relation to retrieve layer-average rain rates from a vertically pointing Ka-band radar and showed that relative retrieval errors generally increase for lighter rainfall when reflectivity changes due to attenuation become smaller compared to vertical changes of non-attenuated reflectivity.…”
Section: A-r Based Rain Rate Estimationmentioning
confidence: 99%
“…The attenuation Z K linearly depends on CLWP because cloud droplets, which are generally smaller than 50 µm, are within the Rayleigh scattering regime for radar wavelengths, so there is a linear relation between cloud liquid water content and the attenuation coefficient. The linearity of the K a -band attenuation coefficient in rain as a function of rain rate is due to the proportionality of both these quantities to the similar moments of rain DSDs (e.g., Matrosov et al, 2006). The expressions for the coefficients C K and B K are given by Matrosov (2009a).…”
Section: An Approach To Retrieve Cloud and Rain Parameters From Mmcr mentioning
confidence: 99%
“…Note that K a band rain attenuation and K a and W band liquid water cloud attenuations do not exhibit significant variability due to DSD details [e.g., Matrosov, 2005;Matrosov et al, 2006]. The JWD DSD estimates are corrected for dead-time effects [Sheppard and Joe, 1994], which brings the disdrometer estimates of total rainfall accumulation to a close agreement with measurements from the standard rain gauge deployed near the JWD.…”
mentioning
confidence: 95%